EVOLUTION OF THE REGIONAL APPROACH IN THE ESCUELA DE GEOGRAFÍA OF THE UNIVERSIDAD DE COSTA RICA: BETWEEN THE INSTITUTIONAL CONTEXT AND THE DISCIPLINARY TRADITION - Vargas Picado, Huberth (2025)
The regional approach in Geography has lost relevance in recent decades, posing a challenge for its integration into academic training and research. This study addresses this issue from a historical-institutional perspective, focusing on how the academic, curricular, and organizational evolution of the School of Geography at the University of Costa Rica has influenced theoretical approaches to the concept of region. A qualitative methodology was applied, based on the documentary analysis of historical and academic sources. The results reveal a transition from descriptive approaches to more analytical and quantitative perspectives, as well as a conceptual renewal aimed at addressing contemporary socio-environmental challenges. The study concludes that, despite existing criticisms, the regional approach remains relevant by integrating physical, sociocultural, and economic dimensions that enable a multiscalar understanding of territorial complexities.